Combining the Legal and the Social in Sociology of Law An Homage to Reza Banakar - Hydén, Håkan; Cotterrell, Roger; Nelken, David; Schultz, Ulrike (Oñati International Series in Law and Society, 2023)
This open access book pays homage to Reza Banakar, who passed away in August 2020, exploring the many different areas of socio-legal research that he worked on and influenced. It begins with a summary of his career and explains how he sparked a debate on the identity and aims of legal sociology. The book is then split into 5 sections: - Theory, including chapters on normativity and the stepchild controversy; - Methods and interdisciplinarity, illustrating how Banakar encouraged socio-legal scholars to push the boundaries of existing socio-legal knowledge through interdisciplinary imagination and methodological flexibility; - Legal culture, with particular focus on Iran - 2 areas of special interest for Banakar; - Law and science, covering topics such as human rights, the right to life, and the COVID-19 pandemic; and - Applied sociology of law, inspired by Banakar's engagement with empirical research and case studies. As well as honouring Reza Banakar's memory and unique thinking, the book aims to advance the sociology of law by demonstrating the interconnectedness of the legal and the social from a broad range of perspectives. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Lund University Libraries.